The ASEAN services sector and the growth rebalancing model - Rafaelita M. Aldaba; Gloria O. Pasadilla (Asian Development Bank Institute (ADBI), 2010)
The growth rebalancing model, which places the nontradable services sector on center stage, is important to spur on faster growth in this sector and tap its potential to become another engine of growth for ASEAN economies. While ASEAN countries have allocated the bulk of their fiscal stimulus packages to infrastructure spending, the present levels are nevertheless considered insufficient to create a large impact on growth. By focusing on the provision of infrastructure and social services like power, ports, roads, and mass transit, along with health and education, governments can address the large investment backlogs in these sectors. Except for Singapore, ASEAN countries remain protective of their services sectors. To encourage and renew private sector interest in infrastructure investment in the region, governments have an important role to play in creating an enabling environment, particularly in maintaining an efficient and competitive services sector. The growth rebalancing model's emphasis on environmental protection, low carbon growth, and green strategies places the spotlight on new areas of services investment where ASEAN countries could develop market niches. Thus, ASEAN governments should pursue policies that support these new growth areas by encouraging research and development, strengthening mechanisms for the transfer of green technology, and promoting greater private sector participation.
Keywords: L91; L80; F40; 330; Dienstleistungssektor; Infrastrukturinvestition; Branchenentwicklung; ASEAN-Staaten